Women Leaders in China: Looking Back and Moving Forward. (May 2016) - Wang, Jia; Shirmohammadi, Melika
The Problem: Leadership research has received extensive attention; however, leadership research that focuses on women is still not part of the mainstream. Furthermore, our current knowledge about leadership is primarily built upon studies situated in the Western context. As a result, while we know much about leadership in general, our understanding of women leadership in a non-Western setting, specifically in China, is still limited. The Solution: This scoping study was conducted to provide a holistic and balanced picture of women leadership progress in China through a literature review. By focusing on women leaders in China, we intend to extend our current understanding of the leadership phenomenon beyond the Western context and the mainstream research foci. The Stakeholders: Developing women leaders is a collaborative effort, requiring multiple stakeholders. For China, findings from this research will benefit national policymakers, organizational leaders, human resource development practitioners, and women leaders. It will also inform Western organizations and managers who will interact with women leaders in China, as well as all scholars who pursue this line of inquiry.